Deleterious Effects of Cymbopogon nardus (L.) Essential Oil on Life Cycle and Midgut of the Natural Predator Ceraeochrysa claveri (Navás, 1911) (Neuroptera: Chrysopidae) - Caballero-Gallardo, Karina; Scudeler, Elton Luiz [UNESP]; Carvalho dos Santos, Daniela [UNESP]; Stashenko, Elena E.; Olivero-Verbel, Jesus (MDPI, 2023)
Cymbopogon nardus (citronella) essential oil (EO) has been widely used in the cosmetic and food industry due to its repellent and fumigant properties. The aim of this study was to evaluate its effects on the life cycle and midgut morphology of the natural predator Ceraeochrysa claveri. Larvae were fed on sugarcane borer eggs (Diatraea saccharalis) pretreated with citronella EO solutions (1–100 µg/mL in methanol, 5 s) or solvent and air-dried at room temperature for 30 min. Larval and pupal stage duration, the percentage of emergence of the insect, and malformed insects were recorded. One day after adults emerged from their cocoons, adult insects were used to obtain their midgut and analyzed using light microscopy. The chemical composition of C. nardus EO revealed that citronellal (25.3%), citronellol (17.9%), geraniol (11.6%), elemol (6.5%), δ-cadinone (3.6%), and germacrene D (3.4%) were the predominant compounds. Exposure to the EO produced a significant change in development duration for third instar and prepupa of the insect. The observed alterations in the lifecycle included prepupae with no cocoon formation, dead pupa inside the cocoon, and malformed adults. Several injuries in the midgut epithelium of exposed adults were registered, such as detachment of columnar cells leaving only swollen regenerative cells fixed on the basement membrane, and the formation of epithelial folds. In summary, these data suggest that C. nardus oil has adverse effects on the life cycle and midgut morphology of a beneficial predator.
Keywords: essential oil; histology; insect; morphological alterations